Oxygen storage capacity versus catalytic activity of ceria–zirconia solid solutions in CO and HCl oxidation. Issue 9 (5th April 2019) - Sun, Yu; Li, Chenwei; Djerdj, Igor; Khalid, Omeir; Cop, Pascal; Sann, Joachim; Weber, Tim; Werner, Sebastian; Turke, Kevin; Guo, Yanglong; Smarsly, Bernd M.; Over, Herbert
Abstract : Ce x Zr1− x O2 solid solutions were prepared to explore the relationship between oxygen storage capacity and activity of oxidation reactions. Abstract : Ce x Zr1− x O2 solid solutions were prepared as a function of the composition x with constant specific surface area in order to explore the relationship between oxygen storage capacity (OSC) and activity of the oxidation reactions of CO and HCl. The as-prepared Ce x Zr1− x O2 solid solutions were characterized by X-ray diffraction (XRD), Raman spectroscopy (Raman), and X-ray photoelectron spectroscopy (XPS). The complete (or total) oxygen storage capacity ("complete" OSC: OSCc) at 430 °C is shown to be linearly correlated to the CO oxidation activity at 430 °C as a function of the Ce concentration x, thus being compatible with the expected Mars–van-Krevelen mechanism. For the catalytic HCl oxidation reaction at 430 °C the activity is also shown to be linearly correlated to the OSCc with a maximum activity realized with Ce0.8 Zr0.2 O2 . From the linear relationship of oxidation activity of HCl and OSCc (that in turn is linear to the activity of CO oxidation) we conclude that the HCl oxidation reaction over Ce x Zr1− x O2 solid solutions proceeds via the Mars–Van-Krevelen mechanism with the reduction of Ce x Zr1− x O2 being rate-determining.